The Stages of Urbanization Development and Their Historical-Philosophical Analysis - Nizomjonovich, Nodirjon Xolmirzayev (Indonesian Journal Publisher, 2024)
This article discusses the stages of urban development that have occurred throughout our country’s history and their unique characteristics. The stages of development are examined from a historical perspective, with insights provided on their advantages and potential applications in the present day. Additionally, the urbanization stages are analyzed from a philosophical and historical viewpoint, with new stages being proposed.